2010
DOI: 10.1016/j.cam.2009.07.054
|View full text |Cite
|
Sign up to set email alerts
|

Applying numerical continuation to the parameter dependence of solutions of the Schrödinger equation

Abstract: In molecular reactions at the microscopic level the appearance of resonances has an important influence on the reactivity. It is important to predict when a bound state transitions into a resonance and how these transitions depend on various system parameters such as internuclear distances. The dynamics of such systems are described by the time-independent Schrödinger equation and the resonances are modeled by poles of the S-matrix.Using numerical continuation methods and bifurcation theory, techniques which f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In [19] it is shown that this procedure does not introduce false solutions, that is, the zeros of F are precisely the poles of S, and that it eliminates any singularities at k = 0. This is an extension of a similar result for the one-dimensional, singlechannel systems case [17,21].…”
Section: A the Case Of N Channels Equal Thresholdssupporting
confidence: 77%
See 1 more Smart Citation
“…In [19] it is shown that this procedure does not introduce false solutions, that is, the zeros of F are precisely the poles of S, and that it eliminates any singularities at k = 0. This is an extension of a similar result for the one-dimensional, singlechannel systems case [17,21].…”
Section: A the Case Of N Channels Equal Thresholdssupporting
confidence: 77%
“…In [1] it was found, for one-dimensional quantum systems, that it is possible to apply the continuation to a regularized function derived from the S-matrix because that function does satisfy the necessary smoothness conditions. For several realistic potentials the resonances were tracked as parameters in the system were varied.…”
Section: Introductionmentioning
confidence: 99%
“…For single-channel radial problems, as in section 2.1, it was proposed in [1] to use a regularized function rather than the S-matrix itself to converge and to track down bound states and resonances. This function was defined as, per l-channel,…”
Section: Resonances and Regularizationmentioning
confidence: 99%
“…Their properties are summarized as follows. (1) The bound states are situated on the positive imaginary axis and correspond to real, negative (rel. to potential asymptote) energies.…”
Section: Gauss Potential With S-wave and P-wave Couplingmentioning
confidence: 99%
See 1 more Smart Citation